Penggambaran Posisi Sosial melalui Strategi Kesopanan: Analisis pada Teks Drama Macbeth dan Terjemahannya dalam Bahasa Indonesia - Aina Khoirida; Haru Deliana Dewi (Madah: Jurnal Bahasa dan Sastra, 2024)
The study examined the characters' social position in William Shakespeare'sÂ  English play , Macbeth, and its Indonesian translation by means of Brown and Levinson's (1987) politeness strategies. By using the descriptive method and qualitative approach, the analysis focused on comparing direct speech containing politeness markers or language elements that show politeness in ST and TT used by four noble characters. The study focused on the first act of the play. Of the three politeness super-strategies by Brown and Levinson (1987) sought in this study, the bald-on record is the most dominant strategy in ST, while it is the negative politeness in TT. Many of the bald-on records found in the ST change into negative politeness in the TT. The changes occured in the social position of all characters being analized. This study contributes to the development of politeness studies, especially in translation and intercultural representation, by offering new perspectives that are relevant to the related literatures.